Nonextraction correction of Class II malocclusion by pendulum appliance - Pallavi Jeetesh Jadhav; Shivprasad Vasant Sonawane; Nikhil Mahajan; Bhushan Gorakh Chavan; Priyanka R Mahale; Rakesh Ashok Pawar (Journal of Pharmacy and Bioallied Sciences, 2021)
A 13-year-old female patient, presented with the chief complaint of forwardly placed upper front teeth. On examination and analysis of relevant records, she was diagnosed as an Angle's Class II malocclusion on a skeletal Class I base. It was decided to treat the patient with a nonextraction treatment approach with the help of maxillary molar distalization followed by fixed mechanotherapy.